miR-3064-5p and miR-4745-5p affect heparin sensitivity in patients undergoing cardiac surgery by regulating AT-III and factor X mRNA levels - Ma, Hai-Ping; Fu, Min; Masula, Maisitanguli; Xing, Chang-Shuang; Zhou, Qiang; Tan, Jing-Tong; Wang, Jiang (Frontiers in Physiology, 2022)
Subject: Perioperative regulation of coagulation function through heparin in patients undergoing cardiac surgery with cardiopulmonary bypass is an important part of performing cardiac surgery, and postoperative bleeding due to abnormal coagulation function caused by differences in heparin sensitivity in different individuals is an independent risk factor for postoperative complications and death. Method: Using an online database, 10 miRNAs interacting with AT-III and FX genes were predicted. Patients were divided into three groups according to the difference in activated clotting time (ACT) after the first dose of heparin (2.5 mg kg−1): group A: hyposensitive group (ACT < 480 s); group B: sensitive group (480 s ≤ ACT ≤ 760 s); and group C: hypersensitive group (ACT > 760 s). Perioperative and 24 h postoperative blood loss and other clinical data of patients in the three groups were recorded. Blood samples were collected before surgery, and RT-PCR was used to detect the levels of AT-III and FX gene mRNA and the levels of predicted 10 miRNAs. Result: Heparin sensitivity was positively correlated with AT-III mRNA levels and negatively correlated with FX gene mRNA levels in the three groups, and the blood loss in group B was significantly lower than that in groups A and C, which was statistically significant (p < 0.05). miR-3064-5p and miR-4745-5p expression levels were significantly different among group A, group B, and group C (p < 0.05) and were closely correlated with AT-III and FX gene mRNA expression levels, respectively. Conclusion: Differences in heparin sensitivity in patients undergoing cardiac surgery were associated with the mRNA expression of AT-III and FX genes, and the expression levels of miR-3064-5p and miR-4745-5p were found to be closely related to the AT-III and FX gene mRNA, respectively, indicating that miR-3064-5p and miR-4745-5p affect the differences in heparin sensitivity among different individuals by regulating the mRNA expression levels of AT-III and FX genes. Clinical Trial Registration:http://www.chictr.org.cn/abouten.aspx, identifier registration number: ChiCTR-2100047348